Respuesta :

Answer:

B

Step-by-step explanation:

The equation of a line in slope- intercept form is

y = mx + c ( m is the slope and c the y- intercept )

Given

4x + 5y = - 45 ( subtract 4x from both sides )

5y = - 4x - 45 ( divide terms by 5 )

y = - [tex]\frac{4}{5}[/tex] x - 9 ← in slope- intercept form

with slope m = - [tex]\frac{4}{5}[/tex]

Given a line with slope m then the slope of a line perpendicular to it is

[tex]m_{perpendicular}[/tex] = - [tex]\frac{1}{m}[/tex] = - [tex]\frac{1}{-\frac{4}{5} }[/tex] = [tex]\frac{5}{4}[/tex] , then

y = [tex]\frac{5}{4}[/tex] x + c ← is the partial equation

To find c substitute (- 4, - 11 ) into the partial equation

- 11 = - 5 + c ⇒ c = - 11 + 5 = - 6

y = [tex]\frac{5}{4}[/tex] x - 6 → B

Answer:

y=5/4x-6

Step-by-step explanation:

4x + 5y = -45 (this is to be perpendicular to the line)

m=5/4 (where m is the gradient of the line)

Write the formula for equation of a line, we have;

y=mx + b

substituting this

y=mx + b

m=5/4, (-4, -11)

substituting

y=mx + b, we have;

-11=5/4 × (-4) + b

solving the equation, we have;

-11=5/4 × (-4) + b

we have;

-11= -5 + b (this is gotten by cancellation of 4 by itself in this -11=5/4 × (-4) + b)

rearrange the unknown term to the left side of the equation:

-11= -5 + b

we have;

-b= -5 + 11 (b is minus because when it cross of the equality sign it (+ sign)changes to (- sign)

-b= -5 + 11,

given us;

-b=6

substituting

y=mx + b

m=5/4 ,b= -6

therefore, y=mx + b

y=5/4x - c